Palliative care in nursing training: higher education course coordinators' perception - Rafaella Guilherme Gonçalves; Luciane Paula Batista Araújo de Oliveira; Carlos Jordão de Assis Silva; Tatiana Maria Nóbrega Elias; Isadora Lorenna Alves Nogueira; Rejane Maria Paiva de Menezes (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to analyze undergraduate nursing course coordinators' perception about nursing training in palliative care. Methods: a descriptive study, with a qualitative approach and thematic content analysis, carried out with coordinators of nursing courses in Higher Education Institutions in Rio Grande do Norte. Results: three thematic categories emerged: Nursing training in palliative care; Potentialities for teaching palliative care; and Challenges of teaching in palliative care. The coordinators described as potentialities: transversality, theoretical and practical approach, optional subject, university extensions, interdisciplinarity and transdisciplinary approach, and as challenges: biomedical model in health education and insufficient professor training. Final Considerations: palliative care teaching in the researched institutions in the nursing education process is approached in an incipient and fragmented way, and almost always without having a specific curricular component on the subject, being present as one of its contents.